Dust bowl girls [large type] : the inspiring story of the team that barnstormed its way to basketball glory - Reeder, Lydia (Thorndike Press, A part of Gale, Cengage Learning, 2017)
At the height of the Great Depression, Sam Babb, the charismatic basketball coach of tiny Oklahoma Presbyterian College, began dreaming. Like so many others, he wanted a reason to have hope. Traveling from farm to farm, he recruited talented, hardworking young women and offered them a chance at a better life: a free college education if they would come play for his basketball team, the Cardinals. Despite their fears of leaving home and the sacrifices faced by their families, the women followed Babb and his dream. He shaped the Cardinals into a formidable team, and something extraordinary began to happen: with passion for the game and heartfelt loyalty to one another and their coach, they won every game.